HUBUNGAN ANTARA KEMAMPUAN PEMAHAMAN MATEMATIK DENGAN KEMANDIRIAN BELAJAR SISWA SMP YANG MENGGUNAKAN PENDEKATAN KONTEKSTUAL - hana rizkia mulianty; Agfie Nurani Hanifah; Asep Ikin Sugandi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The purpose of this study is to examine how the relationship between the ability of mathematical understanding with the independence of student learning in learning using a contextual approach. The method in this research is quasi-experimental method, with two different classes taken, where the first class get learning with contextual approach and second class using ordinary learning. The population is all students in one of the cities cimahi with samples taken two classes. Both classes were given pretest and early questionnaires to determine their initial ability, then in the experimental class were given learning with contextual approach and control class were given regular learning, and at the end of both classes were given postes and also final questionnaire, which the data at the end will be in though and in the correlation analysis using Product Moment Pearson. The results showed a significant relationship between the ability of mathematical understanding and student learning independence in learning mathematics..